ULTRAVIOLET RADIATION DOSIMETRY BY USING OF CN-85 , CR-39, LR-115 NUCLEAR TRACK DETECTORS - Al-Jomaily, Firas; Al-jobouri, Hussain; Mheemeed, Ahmed (Iraqi Journal of Science, 2024)
Ultraviolet radiation dosimetry was determined by using CN-85 , CR-39 ,LR-115 nuclear track detectors – NTD with measuring of ; number of track-NT , etching time-TB , nuclear track diameter - DT and etching velocity -VD . By this study appear the increasing in etching time-TB of NTD samples which irradiated by UV-radiation do not pure effect on the number of track - NT , comparing with un-irradiated samples . The increasing in UV-irradiation make decreasing in etching time- Topt for CR-39 , CN-85 , LR-115 nuclear track detectors with percent of 20% , 25% , 50% respectively , comparing with un– irradiated sample at the radiation dose 3.77x103 erg /mm2 . . The increasing of irradiation dose make increasing in nuclear track diameter-DT with increase in etching time-TB at the radiation dose 300x103erg / mm2 for LR-115 detector . This study showing there was increasing in the percent value of etching velocity -VB with increasing inradiation dose for CR-39 , CN-85 . The increasing in nuclear track diameter- DTwith increasing in radiation dose was appearing as a resulted of energy of radiationand producted free radicals which interact with chemical etching solution . Thisstudy optioned by using nuclear track detectors CN-85 , CR-39 for determinationthe radiation dosimetry through measuring of etching velocity -VB butter than LR-115 detector